Comparing the effects of computerized versus manual methods of identifying point-specific acupuncture as an adjunct to physiotherapy in the management of knee osteoarthritis: A randomized controlled trial protocol - Lee Chai Li; Mohd Azzuan Ahmad; Tan Chee Hou; Angeline Low Ann Je; Lee Zi Lin; Tay Yan Ling; Peng Yan (PLoS ONE, 2025)
Background Knee osteoarthritis (KOA) is a prevalent condition causing significant pain and functional impairment. Acupuncture has shown promise as an adjunctive therapy, but conventional manual selection of acupoints lacks standardization. The Acugraph system provides a computerized method for identifying acupoints, potentially enhancing treatment precision. Objective This study aims to compare the effects of computerized Acugraph-guided acupuncture versus manually selected acupuncture as adjuncts to physiotherapy in managing KOA. Methods A randomized, double-blind controlled trial will be conducted with 50 participants diagnosed with mild to moderate KOA. Participants will be randomly assigned to one of two groups: Group 1 Comp-AcuPhysio (n = 25), receiving Acugraph-guided acupuncture with physiotherapy, or Group 2 Man-AcuPhysio (n = 25), receiving manually selected acupuncture with physiotherapy. Both groups will undergo 12 weekly treatment sessions, each lasting 60 minutes. Outcome measures, including the Knee Injury and Osteoarthritis Outcome Score, active knee flexion range, Timed Up and Go test, Visual Analog Scale for pain, Short Form-36 health survey, and Personal Integrated Energetics score, will be assessed at baseline and immediately post-intervention. An intention-to-treat analysis will be applied. Changes from baseline to 12 weeks will be analyzed using repeated measures analysis of variance for both within-group and between-group comparisons. Results This study will provide a definitive assessment of the effectiveness of computerized Acugraph-guided acupuncture compared to manually selected acupuncture as supplementary treatments alongside KOA physiotherapeutic rehabilitation. Conclusion This trial will offer insights into how incorporating technology-driven approaches, such as Acugraph, with physiotherapy can enhance the customization and effectiveness of KOA management, leading to improved clinical outcomes. These results could advocate for the integration of technological tools in acupuncture to boost treatment precision and efficacy for KOA. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN12624000646549p).